Differentiated stimulating effects of activated carbon on methanogenic degradation of acetate, propionate and butyrate. (June 2018) - Xu, Suyun; Han, Runqi; Zhang, Yuchen; He, Chuanqiu; Liu, Hongbo
Graphical abstract: Highlights: Anaerobic digesters with varied GAC dosages were compared at low and high OLRs. Methanogenic degradation of acetate was almost unaffected by GAC addition. GAC dose-dependent enhancing effect was found for syntrophic HPr/HBu degradation. GAC stimulated the enrichment of syntrophic bacteria . Abstract: Granular activated carbon (GAC) could promote methane production from organic wastes, but a wide range of dosages has been reported. In present study, different GAC dosages of 0, 0.5, 5 and 25 g/L were supplemented into anaerobic digesters and the methanogenic degradation kinetics of acetate, propionate and butyrate were characterized, respectively. At high organic load of 5 g/L, the degradation rates of propionate and butyrate increased by 1.5–4.7 and 2.5–7.0 times at varied GAC dosages. The methane production rates ( Rmax ) from propionate and butyrate were significantly elevated when increasing GAC dosage up to 5 g/L. However, only a minor increment was found for acetate degradation either at 1 g/L or 5 g/L. The stimulatory mechanism of GAC for accelerated syntrophic degradation of propionate and butyrate can be primarily attributed to the triggering effect on acetogenesis, as evidenced by the enrichment of syntrophic bacteria e.g. Thermovirga, Synergistaceae, and Syntrophomonas etc.